Triptolide overcome autocrine Growth Hormone (GH) Mediated Resistance in a Dose-Dependent Manner in MDA-MB-453 Breast Cancer Cells Via Acting on EMT Pathway - Malcanlı, S; Ozkurt, E.; Palavan Unsal, N.; Coker Gürkan, A.; ŞAHİN, BURCU AYHAN; YERLİKAYA, PINAR OBAKAN; ARISAN, ELİF DAMLA (My University, 2019)
Breast cancer is one o f the most common cancer types among women. Beyond environmental and genetic risk factors such as age and genetic background, many growth factors (e.g. VEGF) and hormones (estrogen) are known to affect the development o f breast cancer. Recently, autocrine growth hormone (GH), an essential hormone affecting post-natal growth, has been shown to trigger cell proliferation, invasion, metastasis, and also lead to drag resistance. Upregulation of GH and its receptor (GHR) expression was determined in mammary carcinoma cells. Forced GH expression induced drag resistance against tamoxifen, doxorubicin, mitomycin and curcumin in MCF-7, T47D and BT^I74 breast cancer cells. Triptolide is a diterpenoid triepoxide which have been demonstrated to have multiple biological activities and also triggers apoptotic cell death in breast cancer cells. In this study, our aim was to investigate the role of epithelial-mesenchymal transition (EMT) signalling during triptolide-induccd apoptotic cell death in MDA-MB-453 wt and GH+ breast cancer cells. Triptolide decreased cell viability in a dose-dependent manner, mitochondrial membrane potential loss and nuclear fragmentation were observed. 20 nM triptolide decreased cell viability by 25% and 15% in MDA-MB-453 wt and GH+ cells, respectively. Although autocrine GH expression triggered cell proliferation and colony formation in MDA-MB-453 cells, triptolide (20 nM) treatment suppressed forced GH-mediated invasion and metastasis. Furthermore, autocrine GH mediated aggressive profile was prevented by triprolide treatment through Slug, N-cadherin, Vimentin downregulation within 24 h. Triptolid induced caspase-dependent apoptotic cell death via modulating Bcl-2 family member's expression profile in MDA-MB-453. In consequence, autocrine GH overexpression increased aggressive phenotype of MDA-MD-453 breast cancer cells, however triptolide treatment overcame this resistance mechanism and induced apoptotic cell death.